The prevalence of the Cryptosporidium parvum among children in Ramadi city - KHADIJA KHLEAF AL-DULAIMI (Tikrit Journal of Pure Science, 2022)
The purpose of this study was to determine the prevalence of Cryptosporidium parvum among children in the city of Ramadi and made a comparison between ziehl -Neelsen method and the ELISA method, which is usually used to diagnose this parasite in Ramadi hospital (administration of Obstetrics and Gynecology Hospital and Ramadi Teaching Hospital).